Stock Price Impact of Net Profit Margin, Return on Asset and Earnings Per Share - Hertina, Dede; Hendayana, Yana; Ichsani, Sakina; Fatihat, Gita; Pratiwi, Leni (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to determine the impact of Share Prices on Net Profit Margin, Return on Assets, and Earning Per Share in Food and Beverage Sub Sector Companies listed on the Indonesia Stock Exchange in 2018?2022. The research method used in this research is descriptive and verification. The population of this research was 39 companies. The sampling technique used was purposive sampling, obtaining a sample of 19 companies with a research period of 5 years. The data analysis used in this research is multiple linear regression analysis. The research results show that partially Net Profit Margin and Earning Per Share have a positive and significant effect on stock prices, while Return On Assets have a negative and insignificant effect on stock prices.